e - National Agriculture Market in India : An Effective Implementation and Farmers’ Attraction Path Model - Bandaru, Ramakrishna (Indian Journal of Marketing, 2019)
The Government of India introduced the electronic National Agriculture Market (e-NAM) system in the Indian agricultural sector on April 14, 2016. It enables the farmers and traders to sell or buy the agriculture produce online all over the country. Initially, 21 markets in 8 states were linked with the e-NAM portal, and currently, there are 585 markets that are linked to the e-NAM network from 16 states and 2 UTs. The Indian Government is planning to link all agriculture markets in the country with e-NAM by the end of 2025 to double the annual income of the farmers. Though, huge initiatives are taken by the Central government, the system is not implemented properly and farmers are not much attracted to the e-NAM portal. Therefore, the present study focused on the above problem and identified the major factors on which the government has to concentrate for better implementation of e-NAM. The study is based on primary data which were collected from 180 farmers from e-NAM linked markets in Telangana state. The opinion towards the dimensioned factors was utilized for the development of the framework for structural equation modeling using confirmatory factor analysis (CFA). The combined CFA and structural path model were executed with the help of AMOS. The results of the study revealed that awareness, infrastructure, and investment support dimensions had a positive association with effective implementation of e-NAM in India.